Ibn Al-Arabi – A Prominent Representative Of Sufism - Mirzayev Axrorjon Azamovich (Indonesian Journal Publisher, 2025)
This study explores the life, teachings, and philosophical contributions of Ibn al-Arabi, a prominent figure in Sufism. The research aims to analyze his theological perspectives, particularly his concept of Wahdat al-Wujud (the unity of existence), and its significance in contemporary intellectual discourse.The study employs a historical-philosophical approach to examine Ibn al-Arabi’s works in their socio-cultural context. Comparative analysis is used to contrast his teachings with other Sufi scholars such as Rumi and Jili. Additionally, a philosophical-anthropological method is applied to interpret his views on human existence and spiritual development. The findings highlight Ibn al-Arabi’s profound influence on Islamic philosophy and spirituality. His works emphasize the interconnectedness of divine essence and the material world, shaping the Sufi intellectual tradition. The study also discusses the relevance of his ideas in modern times, particularly in the context of Uzbekistan’s efforts to promote its intellectual heritage.By analyzing Ibn al-Arabi’s doctrines, this research provides new insights into the philosophical and theological foundations of Sufism. It underscores the importance of studying classical Islamic thought to understand contemporary spiritual and intellectual movements.